MORPHOLOGICAL AND ANATOMICAL STUDY OF SHOOTS OF JUNIPERUS COMMUNIS L. FROM CUPRESSACEAE FAMILY - F. K. Serebryanaya; A. S. Shinkarenko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have conducted morphological and anatomical studies of Juniperus communis, revealed diagnostic indices of the stamina, stalk, and needle. The leaf is sessile, linear awe shaped, pointed. Stalk form at cross section is cylindrical. Needles are lanceolar with one whitish vertical stripe, with paracytic stomata.